APLIKASI MAKE UP FLAWLESS DAN MODEL HIJAB DALAM AKTIVITAS SEHARI-HARI - Wahyuningtyas, Fitria; Utami, Dyah Ayu; Wahyuningdyah, Meidya Tri; Ridwan, Agus (Jurnal Abadimas Adi Buana, 2018)
Workshop program and fashionable style competition is a make up and hijab contest. Where the program is held with the intent to provide knowledge for pugeran villagers in the application of flawless make up properly for daily needs. Flawless make up is a perfect makeup that is perfectly smooth. The method of implementation carried out in this activity is to socialize to the residents of each hamlet after that followed by workshop and lombah fashionable style.